Does involvement in corporate social irresponsibility affect the linguistic features of corporate social responsibility reports?. (1st August 2019) - Corciolani, Matteo; Nieri, Federica; Tuan, Annamaria
Abstract: Companies publish corporate social responsibility (CSR) reports to inform their stakeholders of their CSR efforts. However, the literature has shown that these reports can be used as a way to offset companies' involvement in corporate social irresponsibility (CSIR). By relying on a cognitive‐linguistic perspective, we investigate whether firms respond to their own irresponsible business conduct by changing their CSR reports' linguistic features and, if so, how. We use a sample of 135 large corporations headquartered in developed countries between 1995 and 2014. An analysis of their CSR reports reveals that the more a firm is involved in irresponsible business conduct, the more likely it is to use narrative (instead of analytical) and deceptive (instead of authentic) language. Moreover, we show that these two trends are particularly evident for highly internationalised firms.